COMUNICAÇÃO E INOVAÇÃO EM PORTAIS CORPORATIVOS Os casos da Embraer, Natura, Faber-Castell e Rigesa - Falco, Alessandra de (2009)
This paper analyses the relation between communication and innovation in corporate websites of Brazilian companies such as Embraer, Natura, Faber-Castell and Rigesa. These institutions were selected as the central body of this research for being the most innovative of Brazil, according to the first version of the Brazil Index of Innovation (IBI) 2007. The paper will also examine the use of Information and Communication Technologies (ICTs) for the delivery of institutional information and to communicate innovation to the press. The main methodology used is Multiple Case Studies which support the comparison of digital communication through corporate portals. The resources of the Analysis of Content and Discourse Analysis were also used. The survey results show that there is a contradiction between the companies being innovative in products and processes, but not in the planning, management, architecture and dissemination of institutional image.(AU)